ISLAND SOLITUDES - SELFHOOD AND OTHERNESS IN THE POETRY OF MATTHEW ARNOLD AND THOMAS HARDY - More, Octavian (British and American studies : B.A.S, 2019)
Reinforcing the view that the Victorian poetic stance is intimately and inextricably connected with the sphere of ideas, this paper provides an examination of a selection of representative titles by Matthew Arnold and Thomas Hardy, in an attempt to highlight the similarities and differences regarding the poets’ treatment of the seminal dialectic between selfhood and otherness, perception and experience, engagement and ascetic distancing.